Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Produktivitas Kerja Karyawan PT. Finaccel Finance Indonesia - Khaterine Maleva; Hery Wihasnanto (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
The purpose to analyze the influence of leadership style and work discipline on employee work productivity at PT. PT. Finaccel Finance Indonesia. This research is included in the category of causal associative research using a quantitative approach. The population in this study were employees work productivity of PT. Finaccel Finance Indonesia (Kredivo Jakarta Barat.) The technique used for sampling is simple random sampling.The analytical method uses partially and simultaneous linear regression analysis. The results of the research show that in partially and simultaneous ways leadership style and work discipline have a positive and significant effect on employee work productivity at PT. Finaccel Finance Indonesia (Kredivo Jakarta Barat).